Specificity of strength training modes in prepubescent females - Isaacs, L. D.; Pohlman, R. L. (Medicine & Science in Sports & Exercise, 1995)
The effect of an isoinertial (isotonic) strength training program on isometric strength in prepubescent females was investigated. An experimental and control group were used. The training response was different to that of previously published work with prepubescent males. Throughout the change and detraining phases of the study, there was no change in isometric measures or positions. Implication: The specificity of strength training may operate differently in prepubescent females than in males.